Sistem Penggarap Sawah Secara Gilir Ganti Menurut Hukum Adat Desa Tanjung Mudo Penawar Kecamatan Sitinjau Laut Kabupaten Kerinci - Abdul Hariss; Nur Fauziah (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The background of this research is the existence of disputes between rice field owners who are still within the scope of their own families. The formulation of the problem in this study is whether the shift-shifting system of cultivating rice fields in Tanjung Mudo Penawar Village, Kerinci Regency is still implemented according to the provisions of customary law and what are the factors that influence the implementation of the shift-change system of cultivating rice fields according to customary law in Tanjung Mudo Penawar Village, Kerinci Regency. This study aims to determine and analyze the implementation of the system of cultivating rice fields in shifts according to the customary law of Tanjung Mudo Penawar Village, Kerinci Regency. The research method used is empirical juridical, which is a legal research method that functions to see in a real sense and examine how the law works in the community. So that this is also the effectiveness that occurs in the field for the implementation of the shifting system of cultivating rice fields in Tanjung Mudo Penawar Village, Kerinci Regency. The results showed 3 cases so that there were 6 respondents in this study. In these 3 cases there is 1 case whose solution is slightly different. This makes the problem more complicated, so it invites the customary head to solve this case. Then 2 more cases were resolved according to the customary law of Tanjug Mudo Penawar Village, Kerinci Regency and could be resolved amicably. The conclusion of this problem has not been implemented in accordance with the customary provisions of Tanjung Mudo Penawar Village. This is due to several factors.